2016
DOI: 10.1159/000448372
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Group Size Is Related to Seasonal Variation in Neuropeptide Receptor Density

Abstract: In many species, seasonal variation in grouping behavior is widespread, with shifts towards territoriality in the breeding season and grouping in the winter. Compared to the hormonal and neural mechanisms of seasonal territorial aggression, the mechanisms that promote seasonal grouping have received little attention. We collected brains in spring and winter from wild-caught males of two species of emberizid sparrows that seasonally flock (the field sparrow, Spizella pusilla, and the dark-eyed junco, Junco hyem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 76 publications
(98 reference statements)
2
26
0
Order By: Relevance
“…Leung et al (2009; reported that RA capsular labeling was absent in adult zebra finches; instead, the arcopallium labeling seen in adults resembled what we saw here in P75-95 juveniles. Notably, the distinctive 125 I-OVTA labeling in capsular RA that we see here in young zebra finches was previously described in adults of several seasonally breeding species, including canaries (Voorhuis et al, 1990), house sparrows (Ondrasek et al, 2018), European starlings (Ondrasek et al, 2018), dark-eyed juncos (Wilson et al, 2016), and white-throated sparrows (Leung et al, 2009). In seasonal species, song can become highly variable, not unlike plastic song, Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Leung et al (2009; reported that RA capsular labeling was absent in adult zebra finches; instead, the arcopallium labeling seen in adults resembled what we saw here in P75-95 juveniles. Notably, the distinctive 125 I-OVTA labeling in capsular RA that we see here in young zebra finches was previously described in adults of several seasonally breeding species, including canaries (Voorhuis et al, 1990), house sparrows (Ondrasek et al, 2018), European starlings (Ondrasek et al, 2018), dark-eyed juncos (Wilson et al, 2016), and white-throated sparrows (Leung et al, 2009). In seasonal species, song can become highly variable, not unlike plastic song, Fig.…”
Section: Discussionsupporting
confidence: 67%
“…There is evidence, however, that in zebra finches, vasotocin (AVT) neurons in the BSTM strongly promote the tendency of these birds to prefer large groups (Kelly et al., ). Moreover, density of the vasotocin receptor subtype 3 / Oxytocin‐like receptor (VT3) receptor (see Table ) increases in the winter in the field sparrow and dark‐eyed junco, species that flock during this season (Wilson, Goodson, & Kingsbury, ). All together, although in male chickens BSTM AVT neurons respond to social stimuli of positive valence this appears to be restricted to courtship, and VT3 receptor density increases during seasonal flocking in songbirds and this relies on affiliative behaviour, whether and how these findings relate to early affiliative social experiences is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the domestic chick ( Gallus gallus), both the lateral septum and the avian partial homolog of the medial amygdala, the nucleus taeniae, are selectively responsive to features of predisposed stimuli (Lorenzi et al., ; Mayer, Rosa‐Salva, Loveland, & Vallortigara, ; Mayer, Rosa‐Salva, & Vallortigara, ) and these brain nuclei are known to express nonapeptide receptors in several species, including the chicken (Goodson, Schrock, Klatt, Kabelik, & Kingsbury, ; Leung et al., ; Ondrasek et al., ; Selvam, Jurkevich, & Kuenzel, ; Wilson et al., ). Therefore, it is reasonable to suggest that nonapeptide signalling in these brain nuclei may also be important for initiating the process of imprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of nonapeptide receptors by endogenous mesotocin also promotes social behaviour (preferences for larger groups) and the preference for familiar social partners in the gregarious zebra finch . Antagonism of oxytocin receptors also reduces the preference for larger groups in finches .…”
Section: Birdsmentioning
confidence: 99%
“…Grouping behaviour follows seasonal variation in many bird species, with shifts towards territoriality in the breeding season and grouping in the winter. The receptor densities in various brain regions vary seasonally, particularly the densities of receptors for the neuropeptides vasotocin, corticotrophin‐releasing hormone and vasoactive intestinal polypeptide (VIP), and VIP receptor density is associated with seasonal flocking …”
Section: Birdsmentioning
confidence: 99%